Robotic Sponge and Watercolor Painting Based on Image-Processing and Contour-Filling Algorithms - Lorenzo Scalera; Giona Canever; Stefano Seriani; Alessandro Gasparetto; Paolo Gallina (Actuators, 2022)
In this paper, the implementation of a robotic painting system using a sponge and the watercolor painting technique is presented. A collection of tools for calibration and sponge support operations was designed and built. A contour-filling algorithm was developed, which defines the sponge positions and orientations in order to color the contour of a generic image. Finally, the proposed robotic system was employed to realize a painting combining etching and watercolor techniques. To the best of our knowledge, this is the first example of robotic painting that uses the watercolor technique and a sponge as the painting media.